2016
DOI: 10.17738/ajes.2016.0005
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing regional groundwater flow in the Ethiopian Rift: A multimodel approach applied to Gidabo River Basin

Abstract: Being located in the tectonically active Ethiopian Rift, the hydrogeology of the Gidabo River Basin is complex due to the disruption of lithologies by faults and the variability and lateral discontinuity of the aquifers. Hydrogeochemical and isotopic data suggest that the aquifers within the rift floor receive a relevant contribution of groundwater recharged in the highland. However, the incomplete knowledge about the aquifer properties, the hydraulic behavior of the faults, and the boundary conditions cause u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…They then applied this MBR as a boundary condition to a groundwater flow model of the adjacent basin-fill aquifer in the Tobacco Root Basin, MT, and found that MBR accounts for 36% of basin-fill aquifer recharge. Similarly, Mechal et al (2016) estimated recharge to the Gidabo River Basin in the Ethiopian rift valley using a semidistributed soil water model and then applied those values as recharge to a groundwater flow model. They estimate MBR composes 35% of recharge to the rift basin and found that including faults acting as both flow barriers and conduits improved model fit.…”
Section: 1029/2019wr025676mentioning
confidence: 99%
“…They then applied this MBR as a boundary condition to a groundwater flow model of the adjacent basin-fill aquifer in the Tobacco Root Basin, MT, and found that MBR accounts for 36% of basin-fill aquifer recharge. Similarly, Mechal et al (2016) estimated recharge to the Gidabo River Basin in the Ethiopian rift valley using a semidistributed soil water model and then applied those values as recharge to a groundwater flow model. They estimate MBR composes 35% of recharge to the rift basin and found that including faults acting as both flow barriers and conduits improved model fit.…”
Section: 1029/2019wr025676mentioning
confidence: 99%
“…Close to Lake Abaya however, the equipotential lines appear to indicate groundwater flow toward an area south of where the river flows into the lake. Mechal et al (2016) therefore assumed that the groundwater basin does not coincide with the surface-water divide in this area but extends further southward along the lake. Groundwater flow in this part of the catchment appears to be affected by the faults (see geological structures in Fig.…”
Section: Groundwater Levelmentioning
confidence: 99%
“…The results of a highly simplified 2D groundwater model of Gidabo River Basin (Mechal et al 2016) also suggest that the rift floor aquifers receive a significant contribution of groundwater flow from the highland and escarpment (mountain-block recharge).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Consequently, the F11 fault zone partially impedes groundwater flow from flowing south, likely acting as a combined "conduit-barrier." Similar flow behavior and discontinuity in permeability of faults have been examined with numerical modelling (Mechal et al, 2016) and field investigation (Caine et al, 2017). The large discontinuity of the fault in the eastern Española Basin, Rio Grande rift, New Mexico, indicated that it was unlikely to systematically impede groundwater flow (Caine et al, 2017).…”
Section: Permeability and Flow Behaviors In Fault Zonesmentioning
confidence: 75%